Differential Subordinations for Certain Class of Symmetric Functions - Wanas, Abbas Kareem (Journal of Global Research in Mathematical Archives(JGRMA), 2014)
The object of this paper is to introduce and study a new class ð¿ð‘š (ðœ‚; h) of symmetric analytic functions in the open unit disk. Also we obtain some results for this class.